Nonlinear seismic behavior of a masonry hospital over 80 years old reinforced with electro welded mesh - Balvin, Yuri Huaringa (2023)
The seismic silence of the Peruvian coast shows the need to evaluate essential old structures such as schools and hospitals on this area. This type of infrastructure should keep being operational despite a large earthquake. Therefore, it is necessary to reinforce them since they do not meet current seismic design codes. It is shown the performance of a retrofitted masonry hospital made by two different types of brick, clay and adobe or rammed earth material. The retrofitted process consisted of strengthening the slender clay artisanal masonry walls with electro welded mesh, keeping the robust and thick adobe walls with no reinforcement. Due the structural assessment it was found that adobe walls were stiff enough to carry out lateral loads and short lateral displacement, however the clay masonry walls need to be strengthened specially by shear actions. The results of this research show that the retrofitted infrastructure is partially effective as it improves the shear capacity (30% on the longitudinal X axis and 16% on the transverse Y axis) and displacement of the structure; however, early shear hinges are still evident, which shows that the structure continues to maintain a fragile behavior On the other hand, the percentage of improvement differs in both axes since more walls were reinforced in the X axis than in the Y axis. As well it was reached a lateral stiffness improving for both directions of the hospital.